Methodological strategy for teaching social studies in the fourth grade of basic base in interactive animation (Encuentros, 2020)
In Ecuador, social sciences show how society lives in time and space. A methodological proposal was developed for the teaching of social studies in the 4th grade of General Basic Education, through the application of interactive animation at the “General Eloy Alfaro Delgado” school located in the Ambato area. Through a quantitative approach and a descriptive analysis, a survey comprising 33 questions was conducted among 62 students. This was done as a non-experimental transversal approach, consisting of one variable. The data indicated that teacher training is not adequate and the methodology and learning strategies and the environment in the classroom were moderately adequate. It is necessary to train the teacher in multimedia. The proposal provides guidelines for applying interactive animation as an educational tool.Keywords: interactive animation, social sciences, teaching, learning